PENGARUH PERKECAMBAHAN TERHADAP KOMPOSISI ASAM AMINO BIJI MUNGGUR (Enterolobium saman) - , SITI NURAINI; , Prof. Dr. Ir. Sutardi, M.App. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Study on the effects of germination on free amino acids content of mungur beans sprout has been conducted. Dry munggur beans was soaked for 24 hours before germination proceed. Germination process was done for 4 days, and samples for analysis purposes were taken every 24 hours and freeze dried. Either dry munggur beans and munggur beans sprout were analyzed their amino acids content by using HPLC method. The results showed that 15 amino acids in dry munggur beans and munggur beans sprout were detected such as aspartic acid, glutamic acid, serine, histidine, glycine, arginine, alanine, tyrosine, proline, methionine, valine, phenylalanine, isoleucine, leucine, and lysine, and 8 amino acids are belong to essential amino acids. The amount of free amino acid in dry munggur beans and munggur beans sprout were 25.17 and 31.01 % (db), respectively. There was incresing of free amino acids content of munggur beans sprout 23.20% compared with the free amino acids content of dry munggur beans.